Restorative Justice in Narcotics Crimes Investigation: Implementation, Challenges and Obstacles - Tri Imam Munandar; Elizabeth Siregar; Dessy Rakhmawati; Zulham Adamy (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
This article aims to analyse the application of Restorative Justice in investigating narcotics crimes in the Jambi Police Jurisdiction and the obstacles encountered. The approach of restorative justice in the investigation of narcotics crimes in Indonesia is becoming increasingly popular, specifically in the context of handling addicts and victims of narcotics abuse to restore the conditions before the crime occurred, with a focus on rehabilitation and restoration of the relationship between perpetrators and victims (victimless). As empirical juridical research, this article refers to observing the operation of law in society. The results of this study indicate that the application of restorative justice for narcotic abusers must be carried out by referring to the criteria established in the National Police Regulation (Perkapolri) No. 8 of 2021 at the request of the family concerned, followed by an assessment of the perpetrator. However, there are impediments to implementing Restorative Justice, such as a lack of human resources with specific competencies and qualifications, as well as a lack of facilities for narcotics law enforcement at the Jambi Police Narcotics Unit. Therefore, considering that the application of Restorative Justice is time-limited, intense cooperation is needed for all parties who conduct assessments related to scheduling and human resources so that the application of restorative justice can be carried out in time. Furthermore, the Jambi Police Narcotics Unit's support facilities for law enforcement of narcotics crimes must be enhanced further to facilitate the realization of restorative justice.